Creating a Resilient Ecosystem for the Employment of Autistic Individuals: From Understanding to Action. Issue 4 (October 2021) - Klag, Malvina; Nicholas, David; Métayer, Solène
Inspired by a 2020 collective awakening to societal inequalities, we introduce a conceptual framework to address systemic issues around employment for one of society's vulnerable populations—people with autism. We do so as advocates, researchers, practitioners, a family member for one author, and an autistic individual for one author. We first draw upon ecological systems theory to develop a portrait of the complex ecosystem of employment for autistic individuals that reveals multilevel and interconnected influencing elements. We then apply learning from systems and resilience thinking to deepen understanding about how positive change can occur in such an ecosystem. Overall, we propose new paradigms, questions, and actions toward transformative change for this and other systemic challenges faced by vulnerable populations.